IPTV user’s on-demand behavior based on adaptive segmental stretched exponential model - Buhua CHEN; Ge CHEN; Jie LIANG (Dianxin kexue)
The IPTV user’s on-demand behavior model based on adaptive segmental stretched exponential (ASSE) was proposed to optimize the configuration of IPTV CDN system,to improve the video scheduling and storage strategy,and to provide users with better experience for video access.At the same time,the probability of the video access by using the actual IPTV user’s on-demand data of China Telecom was simulated.Experiments show that compared with the traditional modeling methods,the ASSE model proposed not only achieves the purpose of simplifying the mathematical model and reducing the computation,but also improves the accuracy of the curve fitting.It has good consistency with the actual data.